Potensi Ekstrak Etanol Daun Sirih Merah (Piper crocatum) Sebagai Antimikrobakterium - FARIDA JULIANTINA RACHMAWATY; BARMAWI HISYAM; MARSETYAWAN HNE SOESATYO; TRI WIBAWA (Fakultas Farmasi Universitas Pancasila, 2013)
: The incidence of tuberculosis in Indonesia is high. There is a tendency for some people to use herbs for the treatment of tuberculosis. This research aims to investigate the potency of antimycobacterium property of red betel Vine (Piper crocatum) ethanolic extract against Mycobacterium tuberculosis (M. tuberculosis). The red betel vine leaf was extracted using standard ethanol solvent. The extract was tested on Mycobacterium tuberculosis H3 7Rv. The experiment was conducted by using serial dilution method with 50%, 40%, 25%, 20%, 12.5%, 10%, and 6.25% red betel vine ethanolic extract in Middlebrook 7H9 medium and subseqently inoculated into Lowenstein Jensen (LJ) medium. The result was analyzed descriptively by observing the minimum bactericidal concentration (MBC). The experiment was repeated three times to obtain consistent result. There is no bacterial growth in LJ media at concentrations of 50%, 40%, 25%, 20%, 12.5%, and 10% of red betel vine ethanolic extract. The bacteria was able to grow only at the concentration of 6.25% red betel vine ethanolic extract. Thus the ethanolic extract of red betel vine (Piper crocatum) indicates an antimycobaterium activity against M. tuberculosis H37Rv. The MBC is found at the concentration of 10%.